INFORMATION COMMUNICATION TECHNOLOGY MEDIATION ON SUPPLIER RELATIONSHIP MANAGEMENT AND ORGANISATIONAL PERFORMANCE - Denhere, Emmanuel Taengwa; Chikazhe, Lovemore; Kanyepe, James (Business Management Analysis Journal (BMAJ), 2024)
This study sought to assess the mediation effect caused by information communication technology on supplier relationship management and organizational performance. RAOSOFT sample size calculator was used to calculate the sample size of 160 employees from firms in the packaging printing industry in Harare, Zimbabwe. A cross-sectional survey design was adopted for the study. Supplier relationship management was found to positively influence the adoption of information communication technology. Moreover, the mediating role of information communication technology on the relationship between supplier relationship management and organizational performance was also established. The study adds to existing supply chain body of knowledge as it explores the mediation role of information communication technology to supplier relationship management and organizational performance. The results corroborate earlier studies that focused on the relationships between information communication technology and organizational performance.  The study was focused to the packaging printing industry in Harare Zimbabwe, thus affecting the generalisation of the findings. Therefore, future studies on the mediation effect of ICT on SRM and organizational performance should be conducted in other industries in Zimbabwe and the Southern Africa region.